Taxonomic revision of Plesianthidium Cameron (Apoidea: Megachilidae: Anthidiini), an endemic southern African bee genus - Eardley, Connal; Griswold, Terry (Zootaxa, 2015)
The southern African bee genus Plesianthidium Cameron is revised. It comprises twelve species. Two new species are described: Plesianthidium (Spinanthidium) richtersveldense sp. nov. (Namibia and South Africa) and P. (S.) namaquaense sp. nov. (South Africa). Two species, Plesianthidium calvini (Cockerell, 1932) and P. rufocaudatum (Friese, 1909), are reinstated as valid species. Keys for the identification of the species of Plesianthidium are given.